2023
DOI: 10.1093/jac/dkad195
|View full text |Cite
|
Sign up to set email alerts
|

Limited emergence of resistance to integrase strand transfer inhibitors (INSTIs) in ART-experienced participants failing dolutegravir-based antiretroviral therapy: a cross-sectional analysis of a Northeast Nigerian cohort

Adam Abdullahi,
Ibrahim Musa Kida,
Umar Abdullahi Maina
et al.

Abstract: Background Due to the high prevalence of resistance to NNRTI-based ART since 2018, consolidated recommendations from the WHO have indicated dolutegravir as the preferred drug of choice for HIV treatment globally. There is a paucity of resistance outcome data from HIV-1 non-B subtypes circulating across West Africa. Aims We characterized the mutational profiles of persons living with HIV from a cross-sectional cohort in North-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In a study from Malawi, GRT was performed on 27 samples from more than 6400 individuals with VF [72]. In a study from Nigeria, GRT was performed on 33 samples from 281 individuals with VF [73]. In three studies from Tanzania, GRT was performed in nearly all of the 181 individuals with VF [74–76].…”
Section: Resultsmentioning
confidence: 99%
“…In a study from Malawi, GRT was performed on 27 samples from more than 6400 individuals with VF [72]. In a study from Nigeria, GRT was performed on 33 samples from 281 individuals with VF [73]. In three studies from Tanzania, GRT was performed in nearly all of the 181 individuals with VF [74–76].…”
Section: Resultsmentioning
confidence: 99%
“…In a study from Malawi, GRT was performed on 27 samples from more than 6400 individuals with VF [ 70 ]. In a study from Nigeria, GRT was performed on 33 samples from 281 individuals with VF [ 71 ]. In three studies from Tanzania, GRT was performed in nearly all of the 181 individuals with VF [ 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…We described six such studies including one from Brazil of 113 PLWH with confirmed VF on a first-line regimen of DTG plus two NRTIs [ 42 ] and five from Sub-Saharan Africa. The studies from Sub-Saharan Africa included approximately 214 individuals, most of whom had prior ART experience before initiating DTG treatment [ 70 , 71 , 72 , 73 , 74 ]. The study from Brazil found that approximately six percent of the samples tested were found to have INSTI DRMs, whereas in the studies from Sub-Saharan Africa, approximately nine percent of the samples tested had INSTI DRMs.…”
Section: Discussionmentioning
confidence: 99%
“…At present, resistance to integrase inhibitors in treatment naïve individuals is very low, with some individuals selecting major INSTI mutations 10 , 46 ; however, ~10% of previously treatment-experienced individuals who go on to develop viremia whilst on an integrase inhibitor harbour INSTI mutations. Ongoing surveillance for INSTI resistance in the DTG treatment era is critical, given the highly promising results from CAB PreP studies 47 , 48 and emerging data showing that the use of LA CAB/RPV during acute HIV infection can result in the selection of major resistance mutations to INSTIs 49 .…”
Section: Discussionmentioning
confidence: 99%